Township-level governance in disaster preparedness in Yangon, Myanmar, during the period of transformation from April 2011 to January 2021 - Zin Mar Than; Hlaing Maw Oo; Sophie-Bo Heinkel; Toe Aung; Tin Tin Kyi; Saw Sandar Oo; Win Lei Mar; Win Maung; Zin Nwe Myint; Khin Khin Soe; Marlene Willkomm; Christian Miller; et al. (Natural Hazards, 2026)
Since Cyclone Nargis hit the country in 2008, Myanmar has stepped up its efforts to implement a disaster management system aimed at reducing disaster risk. At the same time, a far-reaching political and social transformation took place, shifting from military to civilian administration between April 2011 and January 2021. During this period, new concepts for disaster risk management were developed internationally, focusing on local governance and community-based strategies. This article provides an overview of the legal and organisational framework introduced in Myanmar for disaster risk management during the transition phase. In particular, it examines how and to what extent governance elements have been integrated into the system to meet local societal needs. The focus is on identifying challenges, gaps and opportunities in local governance structures. The study employs a mixed-methods analysis approach. This involved conducting 28 expert interviews with Yangon-based disaster management institution members as well as a quantitative household survey of 896 people in eight Yangon townships. Additionally, an in-depth analysis of government documents and reports was conducted. The study shows that the general framework for implementing governance aspects was already well established when the political system changed again in 2021. In practice, however, governance aspects remain challenging.

DECDNet: A dual encoder change detection network for monitoring mangrove gain and loss using Sentinel-2 data - Win Sithu Maung; Satoshi Tsuyuki; Takuya Hiroshima (Remote Sensing Applications: Society and Environment, 2026)

System shift in rice: Processes and pathways of change in rice-based production systems of Southeast Asia - Mathias Becker; Richelyn Clavero; Ohnmar Min Khin; Sichantha Kong; Zar Ni Maung; Punlork Men; Shyam Pariyar; Manuel José C. Regalado; Sophoanrith Ro; Kyaw Kyaw Win (Agricultural Systems, 2024)

Characterization and health risk assessment of PM2.5-bound polycyclic aromatic hydrocarbons in Yangon and Mandalay of Myanmar - Ning Zhang; Myo Win Maung; Shunyao Wang; Eleonora Aruffo; Jialiang Feng (Science of The Total Environment, 2024)

Polymyxin B neutralizes endotoxin and improves the quality of chicken semen during liquid storage - Ei Ei Win Maung; Pangda Sopha Sushadi; Atsushi Asano (Theriogenology, 2023)

Disaster preparedness and resilience at household level in Yangon, Myanmar - Sophie-Bo Heinkel; Benni Thiebes; Zin Mar Than; Toe Aung; Tin Tin Kyi; Win Lei Mar; Saw Sandar Oo; Christian Miller; Marlene Willkomm; Win Maung; Zin Nwe Myint; Khin Khin Soe; et al. (Natural Hazards, 2022)
Resilience has become important in disaster preparedness and response. Unfortunately, little is known about resilience at the household level. This study presents the results of a survey into individual and household level preparedness to disaster events in Yangon, Myanmar, which is prone to natural disasters such as tropical cyclones, flooding, and earthquakes. The study aimed to understand societal resilience and to provide information that could be used to develop a holistic framework. In four different Yangon townships, 440 households were interviewed. The results of the survey indicate how risk preparedness could be improved by specific measures related to the following five factors: (1) increasing the general public’s knowledge of first aid and its role in preparedness; (2) improving mobile phone infrastructure and capacity building in its usage so that it can be used for communication during disasters, along with building up a redundant communication structure; (3) better use and organisation of volunteer potential; (4) more specific involvement of religious and public buildings for disaster response; and (5) developing specific measures for improving preparedness in urban areas, where the population often has reduced capacities for coping with food supply insufficiencies due to the high and immediate availability of food, shops and goods in regular times. The findings of this survey have led to specific recommendations for Yangon. The identified measures represent a first step in developing a more general framework. Future research could investigate the transferability of these measures to other areas and thus their suitability as a basis for a framework.

Anti-hepatitis B activities of Myanmar medicinal plants: a narrative review of current evidence - Ye Htut Linn; Win Win Ei; Lwin Mon Mon Myint; Khin Maung Lwin (VirusDisease, 2021)

First elemental analysis of glass from Southern Myanmar: replacing the region in the early Maritime Silk Road - Laure Dussubieux; Bérénice Bellina; Win Hsan Oo; U Maung Sun Win; Htet Myet Tut; Kalayar Myat Myat Htwe; Khinsandar Kyaw (Archaeological and Anthropological Sciences, 2020)

Conversion of abandoned paddy fields to productive land through mangrove restoration in Myanmar’s Ayeyarwady Delta - Win Maung Aye; Shinya Takeda (Paddy and Water Environment, 2020)

Political transition and emergent forest‐conservation issues in Myanmar - Graham W. Prescott; William J. Sutherland; Daniel Aguirre; Matthew Baird; Vicky Bowman; Jake Brunner; Grant M. Connette; Martin Cosier; David Dapice; Jose Don T. De Alban; Alex Diment; Julia Fogerite; et al. (Conservation Biology, 2017)
Political and economic transitions have had substantial impacts on forest conservation. Where transitions are underway or anticipated, historical precedent and methods for systematically assessing future trends should be used to anticipate likely threats to forest conservation and design appropriate and prescient policy measures to counteract them. Myanmar is transitioning from an authoritarian, centralized state with a highly regulated economy to a more decentralized and economically liberal democracy and is working to end a long‐running civil war. With these transitions in mind, we used a horizon‐scanning approach to assess the 40 emerging issues most affecting Myanmar's forests, including internal conflict, land‐tenure insecurity, large‐scale agricultural development, demise of state timber enterprises, shortfalls in government revenue and capacity, and opening of new deforestation frontiers with new roads, mines, and hydroelectric dams. Averting these threats will require, for example, overhauling governance models, building capacity, improving infrastructure‐ and energy‐project planning, and reforming land‐tenure and environmental‐protection laws. Although challenges to conservation in Myanmar are daunting, the political transition offers an opportunity for conservationists and researchers to help shape a future that enhances Myanmar's social, economic, and environmental potential while learning and applying lessons from other countries. Our approach and results are relevant to other countries undergoing similar transitions.

Seasonal dynamics influencing coastal primary production and phytoplankton communities along the southern Myanmar coast - Maung-Saw-Htoo-Thaw; Shizuka Ohara; Kazumi Matsuoka; Tatsuya Yurimoto; Shota Higo; Khin-Ko-Lay; Win-Kyaing; Myint-Shwe; Sein-Thaung; Yin-Yin-Htay; Nang-Mya-Han; Khin-Maung-Cho; et al. (Journal of Oceanography, 2017)